Failed Clearance of Aneuploid Embryonic Neural Progenitor Cells Leads to Excess Aneuploidy in the Atm-Deficient But Not the Trp53-Deficient Adult Cerebral Cortex - McConnell, Michael J. (J Neurosci, 2004)
Aneuploid neurons populate the normal adult brain, but the cause and the consequence of chromosome abnormalities in the CNS are poorly defined. In the adult cerebral cortex of three genetic mutants, one of which is a mouse model of the human neurodegenerative disease ataxia-telangiectasia (A-T), we observed divergent levels of sex chromosome (XY) aneuploidy. Although both A-T mutated (Atm)- and transformation related protein 53 (Trp53)-dependent mechanisms are thought to clear newly postmitotic neurons with chromosome abnormalities, we found a 38% increase in the prevalence of XY aneuploidy in the adult Atm(-/-) cerebral cortex and a dramatic 78% decrease in Trp53(-/-) mutant mice. A similar 43% decrease in adult XY aneuploidy was observed in DNA repair-deficient Xrcc5(-/-) mutants. Additional investigation found an elevated incidence of aneuploid embryonic neural progenitor cells (NPCs) in all three mutants, but elevated apoptosis, a likely fate of embryonic NPCs with severe chromosome abnormalities, was observed only in Xrcc5(-/-) mutants. These data lend increasing support to the hypothesis that hereditary mutations such as ATM-deficiency, which render abnormal cells resistant to developmental clearance, can lead to late-manifesting human neurological disorders.